2018
DOI: 10.1071/rd17170
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of melatonin on in vitro embryo production from juvenile goat oocytes

Abstract: Melatonin is a universal antioxidant that improves in vitro embryo production in several species. The aims of this study were to determine the melatonin concentration in the ovarian follicular fluid (FF) of juvenile goats and the effect of melatonin during in vitro maturation (IVM) on embryo development. The FF melatonin concentration was 0.57--1.07×10-9 M, increasing with follicular diameter. Oocytes were matured, fertilised and cultured under conventional conditions. Blastocyst development, embryo quality an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 51 publications
0
23
1
Order By: Relevance
“…Finally, we hypothesized a positive effect of melatonin on embryo development and quality. Contrary to our previous results (Soto‐Heras et al, ) we did not find a higher blastocyst yield with melatonin. Other studies neither found improvement on blastocyst production (Casao et al, ; Rodrigues‐Cunha et al, ; Takada, Martins Junior, Mingoti, Balieiro, & Coelho, ) which denotes a variability in results depending on specific culture conditions.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Finally, we hypothesized a positive effect of melatonin on embryo development and quality. Contrary to our previous results (Soto‐Heras et al, ) we did not find a higher blastocyst yield with melatonin. Other studies neither found improvement on blastocyst production (Casao et al, ; Rodrigues‐Cunha et al, ; Takada, Martins Junior, Mingoti, Balieiro, & Coelho, ) which denotes a variability in results depending on specific culture conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…There is strong evidence of melatonin positive effect on IVEP when is added to IVM medium in cow and sheep (Sampaio et al, ; Tian et al, ). Previous studies in our laboratory showed an increase of blastocyst production and quality by adding 10 −7 M of melatonin to IVM medium of juvenile goats, which denotes its potential for improving JIVET programs (Soto‐Heras et al, ). In this previous study, we also observed that melatonin decreased oocyte ROS levels.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Under in vivo conditions, COCs are provided with all essential minerals, growth factors, proteins, and natural buffering agents that cannot be mimicked totally under in vitro counterparts. However, developmental capabilities of COCs can be improved by supplementation of various hormones, growth factors, serum, cells, follicular fluid, and other substances added to the maturation media (Romero-Arredondo and Seidel, 1996;Choi et al, 2001;Zhou et al, 2016;Soto-Heras et al, 2018). In this context, the blastocyst rate was improved, reaching up to 70% when COCs were matured in vivo, while this rate dropped to 30-35% under IVM conditions (Wrenzycki and Stinshoff, 2013).…”
Section: Introductionmentioning
confidence: 99%